Harry, el perrito sucio - Zion, Gene; Graham, Margaret Bloy; Fiol, Maria A. ([New York, N.Y.] : Harper Arco Iris, 1996)
When a white dog with black spots runs away from home, he gets so dirty his family doesn't recognize him on his return as a black dog with white spots.
Accelerated Reader
Keywords: Dogs -- Juvenile fiction; Perros -- Novela juvenil